Clima organizacional y satisfacción laboral en el cuerpo de bomberos de Latacunga. - Rivadeneira Albarracín, Kevin Mateo (2023)
The objective of the research was to determine the relationship between organizational climate and job satisfaction in the Fire Department in Latacunga city. The final objective is to improve the efficiency of the institution. To achieve this, similar previous research was reviewed to provide a clearer research context. The type of research is descriptive under a quantitative, non-experimental and correlational approach. Two surveys adapted to the study variables (organizational climate and job satisfaction) were applied to 72 workers (26 administrative and 47 operators), obtaining 67 responses, which represents a participation of 93%. When Cronbach's alpha was applied, it was found that the instrument used to collect the information has a high internal consistency, with a scale of 0.913, which guarantees its reliability, in addition, the results of the research were analyzed using Pearson's correlational technique, which provided sufficient statistical evidence of a positive, strong and significant association between the variables (0.83; p-value < 0.05)). Strategies based on the dimensions of the organizational climate are proposed to improve the job satisfaction of the personnel of the Fire Department in Latacunga city.